Proceedings of the Fourteenth Annual ACM-SIAM Symposium on Discrete Algorithms 2020
DOI: 10.1137/1.9781611975994.67
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Distributed Verifiers in Interactive Proofs

Abstract: We explore the power of interactive proofs with a distributed verifier. In this setting, the verifier consists of n nodes and a graph G that defines their communication pattern. The prover is a single entity that communicates with all nodes by short messages. The goal is to verify that the graph G belongs to some language in a small number of rounds, and with small communication bound, i.e., the proof size.This interactive model was introduced by Kol, Oshman and Saxena (PODC 2018) as a generalization of non-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 28 publications
0
47
0
Order By: Relevance
“…This model provides a better understanding of problems such as symmetric dumbbell graphs in Section 4.3, and follow-up works have shown that powerful tools can be designed for this setting, with trade-offs between the different resources (number of bits exchanged, number of prover-nodes communication rounds etc.) [18,57,55].…”
Section: Distributed Decision: a Complexity Theory Point Of Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…This model provides a better understanding of problems such as symmetric dumbbell graphs in Section 4.3, and follow-up works have shown that powerful tools can be designed for this setting, with trade-offs between the different resources (number of bits exchanged, number of prover-nodes communication rounds etc.) [18,57,55].…”
Section: Distributed Decision: a Complexity Theory Point Of Viewmentioning
confidence: 99%
“…This is a recent and active area of research. We refer to [57] for a list of nice open questions. Let us just mention that an important question is to establish the best trade-off possible between interaction and communication.…”
Section: Complexity Theorymentioning
confidence: 99%
“…It is always important to keep in mind the compiler defined in [40] which turns, automatically, any problem solved in NP in time τ (n) into a dMAM protocol that uses bandwidth τ (n) log n/n. Therefore, any class of sparse graphs that can be recognized in linear time, can also be recognized by a dMAM protocol with logarithmic-sized certificates.…”
Section: Related Workmentioning
confidence: 99%
“…However, all predicates on labeled graphs can be certified by allowing randomization [23], or by allowing just one alternation of quantifiers (the analog of Π 2 in the polynomial hierarchy) [8]. A recent line of work studies a distributed variant of interactive proofs [15,33,40].…”
Section: Previous Workmentioning
confidence: 99%